Fluctuations in routine blood count might signal severe immune-related adverse events in melanoma patients treated with nivolumab. Issue 2 (November 2017) - Fujisawa, Yasuhiro; Yoshino, Koji; Otsuka, Atsushi; Funakoshi, Takeru; Fujimura, Taku; Yamamoto, Yuki; Hata, Hiroo; Gosho, Masahiko; Tanaka, Ryota; Yamaguchi, Kei; Nonomura, Yumi; Hirai, Ikuko; et al.
Highlights: Immune-related AEs (irAEs) correlate with changes in routine blood count parameter. WBC count and relative lymphocyte count correlate with severe irAEs. Similarly, those parameters also correlate with lung or gastrointestinal irAEs. Routine blood test may be easy and cost-effective method to detect irAEs. Abstract: Background: Although nivolumab significantly prolongs survival of metastatic melanoma, about 10% of patients experience severe, even fatal immune-related adverse events (irAEs). Biomarkers to predict irAEs are, therefore, of great interest. Objective: We aimed to correlate changes in routine blood count parameters to the occurrence of serious irAEs (grade 3/4 [G3/4] or lung/gastrointestinal [lung/GI] irAEs) in patients with melanoma who were treated with nivolumab. Methods: We retrospectively analyzed data from 101 patient with melanoma treated with nivolumab from 8 institutes in Japan. We used logistic regression analyses to investigate associations between severe irAEs and fluctuations in routine blood count parameters (total white blood cell [WBC] count, relative neutrophil, monocyte, lymphocyte, and eosinophil count) during the treatment. Receiver-operating characteristic curve was used to determine a cutoff value for the blood count parameters and area under the curve (AUC). Results: Univariate analysis revealed that G3/4 irAEs were associated with increased total WBC count ( P = 0.034, cutoff value = +27%, AUC = 0.68, odds ratio [OR] = 1.58) and decreased relative lymphocyte count (RLC, P = 0.042, cutoff value = −23%, AUC = 0.65, OR = 1.65). However, multivariate analysis showed that the same factors, increased WBC count ( P = 0.014, cutoff value = +59.1%, AUC = 0.79, OR = 6.04) and decreased RLC ( P = 0.012, cutoff value = −32.3%, AUC = 0.81, OR = 5.01) were independent factors associated with lung/GI irAEs. Conclusions: Our results suggest that increased WBC count and decreased RLC are associated with G3/4 and lung/GI irAEs. Our analysis was based on the data point at which irAE occurrence was noticed and, therefore, these factors are not predictive, however, they could be a "signal" of severe irAE occurrence in patients with melanoma treated with nivolumab.